Prevalence of leishmaniosis in dogs in Istanbul,Turkey determined by using PCR - BILGIN, Z.; TURAN, N.; YILMAZ, H.; FERROGLIO, E.; TUZER, E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Leishmania infantum is widespread in Mediterranean countries including Turkey and can cause a serious disease in both humans and dogs. Dogs are considered to be its main reservoirs. The current epidemiological study was carried out in Istanbul for detection of leishmaniosis among dogs. A total of 246 dogs were included in the study. Twenty one (8.54%) blood samples were found to be positive based on PCR diagnosis, using primers specific for the kinetoplast DNA of Leishmania. Infection rate was 6.51% in 169 dogs living in shelters and 12.99% in 77 client-owned dogs. The rate was significantly (p<0.001) higher in the dogs (37.93%) presenting one or more clinical symptoms which may be attributable to leishmaniosis, than in the asymptomatic dogs (4.61%). Eleven (52.4%) of 21 PCR positive dogs presented clinical symptoms whereas the rest of the dogs (47.62%) were asymptomatic. The major clinical sign in PCR positive animals was dermatological problems. Amongst PCR positive dogs, skin lesions were present in 11, weight loss in 2, lymphadenopathy in 2, epistaxis in 2 and lethargy in 2 dogs.